DINAMIKA PERIBADATAN GEREJA INJILI DI INDONESIA PASCA KONFLIK TOLIKARA: STUDI KASUS DI DESA MOJOKERTO KECAMATAN KEDAWUNG SRAGEN - MUSTOLEHUDIN MUSTOLEHUDIN (Sekretariat Badan Litbang dan Diklat Kementerian Agama RI, 2017)
Evangelical church named Gereja Injili in Indonesia (GIDI) has been established in Sragen since 1990. Sinceits establishment to the mid-2015, there has been no significant disagreement with the local people. A frictionappeared shortly after Tolikara conflict in July 2015. By employing a qualitative approach, this study finds outthat: first, GIDI in Sragen has not obtained a juridical license according to Joint Ministerial Regulations (PBM)No. 8 and 9 2006. Second, the accusation of Surakarta Muslim Troops (Laskar Umat Islam Surakarta) that GID I created disharmony in the society was proven not true. The church committee maintained a good cooperation with local society in terms of helping them during their celebration ceremonies. KEY WORDS: GID I Sragen, House of Worship, LUIS, FKUB